Factors Related to Husband's Involment in Antenatal Care Visits in High Risk Pregnant Women - Nurhalimah Juneldi; Vaulline Basyir; Rosfita Rasyid; Syamel Muhammad; Rozi Sastra Purna; Hasmiwati (Indonesian Journal of Advanced Research, 2024)
High-risk pregnancy is a pregnancy that can cause harm and complications to the mother and fetus during pregnancy, childbirth or after delivery compared to normal pregnancy and childbirth. The aim of this research is to determine "Factors Associated with Husband's Involvement in Antenatal Care Visits for High Risk Pregnant Women". The design in this research is cross-sectional. The sample in the study was 187 people. The validated questionnaire was used in collecting data for this research. and analyzed univariately using frequency distribution, bivariate using chi-square test, and multivariate using logistic regression test. The research results showed that age (p=0.875), education (p=0.004), income (p=0.015). Based on the multivariate results, it was found that the most dominant factor related to husband's involvement in antenatal care visits was education with the highest OR value of 0.139.